1984
DOI: 10.1007/bf00973033
|View full text |Cite
|
Sign up to set email alerts
|

Extra- and intracellular amino acids in the hippocampus during development of hepatic encephalopathy

Abstract: Fulminant hepatic failure was induced in rabbits by intravenous administration of galactosamine hydrochloride. The animals were sacrificed after 45 h and the hippocampus analyzed for free amino acids. In addition, free amino acids were measured in plasma and in the extracellular fluid of the hippocampus 20, 30 and 45 h after galactosamine injection. The extracellular fluid compartment was analyzed by slow perfusion of a thin dialysis tube which was implanted in the hippocampus one day prior to galactosamine ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
1
4

Year Published

1986
1986
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 20 publications
4
54
1
4
Order By: Relevance
“…Thus, despite findings of increased cerebrospinal fluid and extracellular brain levels of glutamate (6)(7)(8)(9)32), as well as increased brain tissue and cerebrospinal fluid levels of the excitotoxin quinolinic acid in both clinical and experimental hepatic encephalopathy (26,27), we could not demonstrate excitotoxic brain damage in experimental acute hepatic encephalopathy using 45CAC12 autoradiography. The latter technique has been shown to be a sensitive tool to demonstrate cerebral calcium accumulation, in pathological conditions associated with excitotoxicity (19)(20)(21)28).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Thus, despite findings of increased cerebrospinal fluid and extracellular brain levels of glutamate (6)(7)(8)(9)32), as well as increased brain tissue and cerebrospinal fluid levels of the excitotoxin quinolinic acid in both clinical and experimental hepatic encephalopathy (26,27), we could not demonstrate excitotoxic brain damage in experimental acute hepatic encephalopathy using 45CAC12 autoradiography. The latter technique has been shown to be a sensitive tool to demonstrate cerebral calcium accumulation, in pathological conditions associated with excitotoxicity (19)(20)(21)28).…”
Section: Discussioncontrasting
confidence: 56%
“…The latter technique has been shown to be a sensitive tool to demonstrate cerebral calcium accumulation, in pathological conditions associated with excitotoxicity (19)(20)(21)28). Furthermore, increases of extracellular brain glutamate, during cerebral ischemia (3.5-8 fold) (29) and hypoglycemia (2.5 fold) (30), conditions considered to be associated with glutamate-related neurototoxicity, are similar to those found during acute liver failure (6)(7)(8). In addition, hippocampus and striatum were chosen because these brain regions are known to contain a large number of glutamate receptors (33).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Extracellular and vesicular glutamate represent only a small fraction of total brain glutamate. 68,69 Conceivably, lithium at levels generally associated with maintenance therapy may exert an inducing effect on Glu through stimulation of neuronal and glial metabolism, neurogenesis in the hippocampus as well as gliogenesis in the hippocampus and possibly elsewhere in the brain. Along these lines, we have recently reported that glutamate levels in the dorsolateral prefrontal cortex in major depression increase with clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with glutamic acid, the concentrations of glutamine in plasma and cerebrospinal fluid are 1-3 orders of magnitude higher (14,16), whereas those of GABA are at least a magnitude lower or negligible (14,17). However, the concentrations of all three in brain are between 5 and 50 mM (14,16 (19).…”
Section: Discussionmentioning
confidence: 99%